Revisiting the age of the Florisbad hominin material - Lee R. Berger; John Hawks (Homo)
In 1996, Grün and coworkers provided an ESR age determination for a hominin molar from Florisbad, South Africa, at 259 ± 35 ka. The most anatomically informative hominin specimen from Florisbad is a fragmentary craniofacial specimen, attributed by many to early Homo sapiens, which has been assumed to derive from the same individual as this tooth. Since 1996, evidence about the evolutionary context for the later Middle Pleistocene and its associated hominins in Africa had markedly changed. If the Florisbad date is accurate and if the molar is associated with the craniofacial specimen, this evidence may suggest that Homo naledi coexisted in time and geography with H. sapiens in southern Africa. Thus, the accuracy for all dates needs critical investigation. This study examines the published record of excavation and subsequent analyses for the Florisbad material. We find that the contemporary records raise doubt about the contemporaneity of the tooth and calvaria. The site’s complex stratigraphy and the details about the tooth’s discovery also pose challenges for the previous ESR age estimate. Because the fragmentary cranial specimen has value for morphological comparisons, developing additional means of understanding its geological age is necessary. The current data do not demonstrate the presence of H. sapiens in southern Africa at ~260 ka.